Proposta de melhorias nos sistemas estratégicos de avaliação da internacionalização na Universidade Federal do Ceará a partir da abordagem analítica do balanced scorecard - Castro, Davi Thomaz de (2021)
The greater flow of people and information due to globalization has approximated people and increased interdependence in governmental, social, and institutional relations. In this context, internationalization emerges as the way through which governments and institutions adjust strategies to the effects of globalization. In college education, studies on internationalization are essential, as they allow significant contributions to the strategies used and to the management stage of the organizations. Based on the assumption that an effective organization has clear and effective planning, operation and control processes, research on institutional management of internationalization is essential. Considering the case studies of Teixeira (2018) and Nunes (2018) that revealed administrative gaps in the Federal University of Ceará (UFC) and the survey conducted by CAPES (2017), in which a considerable portion of Brazilian Higher Education Institutions (HEIs) demand greater efforts in management, this study proposed improvements in the strategic systems of assessing internationalization at the UFC, from the analytical approach of the balanced scorecard, by Kaplan and Norton (1992), using Rocha’s (2016) roadmap, which recognizes the necessity of evaluative systems of internationalization by Brazilian HEIs and supports the proposal based on the perspectives of Stakeholders, academic mobility, curricular innovation, people development, material, financial and structural resources and organizational change perspective. With this in mind, a qualitative analysis approach was used, of applied nature and descriptive type, in order to identify the institutional guidelines and the perceptions of managers about the theme, as well as to propose performance indicators that enable improvements in the systems of performance measurement in internationalization by the UFC. The findings indicate that the UFC treats internationalization as a priority, but it needs higher control of its evaluation processes. Moreover, the "language" dimension is included as an additional perspective to the evaluation system proposed in this study because it is considered indispensable to the success of internationalization in the UFC.